Preservation of Eoarchean mantle processes in similar to 3.8 Ga peridotite enclaves in the Itsaq Gneiss Complex, southern West Greenland - van de Loecht, J.; Hoffmann, J. E.; Rosing, M. T.; Sprung, P.; Muenker, C. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Eoarchean mantle and mantle-derived rocks can provide primary information on geodynamic processes operating on the early Earth. This study combines new petrological observations, comprehensive major and trace element data as well as Lu-Hf and Sm-Nd isotope compositions of >3.81 Ga ultramafic rocks from the Itsaq Gneiss Complex (IGC) in southern West Greenland. The sample set includes mantle peridotites and associated amphibolites from the Narssaq ultramafic body (Faeringehavn terrane) and from the region south of the Isua supracrustal belt (Isukasia terrane). Lutetium-Hf whole rock age regression lines mainly yield Eoarchean ages of ca. 3.9-3.8 Ga, in good agreement with minimum ages inferred from field relationships (>3.8 Ga). Major and trace element signatures, the Lu-Hf isotope inventory as well as most major elements, MREE, HREE, and HFSE were only slightly disturbed during metamorphic overprint. Nearly flat primitive mantle-normalized REE patterns obtained for the mantle peridotites resemble those of refertilized modern abyssal peridotites and may reflect re-enrichment of initially depleted peridotite by melt-like subduction components, as also indicated by Th-HFSE-REE characteristics. Based on a simple evolution-model for the investigated mantle rocks, we suggest that the compositions are best explained by partial hydrous melt depletion in the spinel stability field, followed by refertilization by low quantities of adakite-like melt. Altogether, the geochemical data can be put in the framework of a geodynamic model, where Eoarchean mantle underwent significant melt extraction and subsequent re-fertilization by subduction-like components. Based on this finding, we propose that the Eoarchean mantle peridotites from SW Greenland represent remnants of a mantle wedge, confirming that subduction-like processes were in operation since at least the Eoarchean. (C) 2020 Elsevier Ltd. All rights reserved.